2011
DOI: 10.1088/0004-637x/730/2/136
|View full text |Cite
|
Sign up to set email alerts
|

FIRST SPECTROSCOPIC MEASUREMENTS OF [O III] EMISSION FROM Lyα SELECTED FIELD GALAXIES ATz∼ 3.1

Abstract: We present the first spectroscopic measurements of the [O iii] 5007Å line in two z ∼ 3.1 Lymanalpha emitting galaxies (LAEs) using the new near-infrared instrument LUCIFER1 on the 8.4m Large Binocular Telescope (LBT). We also describe the optical imaging and spectroscopic observations used to identify these Ly-α emitting galaxies. Using the [O iii] line we have measured accurate systemic redshifts for these two galaxies, and discovered a velocity offset between the [O iii] and Ly-α lines in both, with the Ly-α… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 80 publications
13
122
0
Order By: Relevance
“…For the other three LAEs at z ∼ 2−3 (star symbols), the offsets are 70−270 km s −1 . These values are consistent with previous estimations from McLinden et al (2011) and updated by Chonis et al, priv. comm.).…”
Section: Lyα Emitter Ism Propertiessupporting
confidence: 93%
“…For the other three LAEs at z ∼ 2−3 (star symbols), the offsets are 70−270 km s −1 . These values are consistent with previous estimations from McLinden et al (2011) and updated by Chonis et al, priv. comm.).…”
Section: Lyα Emitter Ism Propertiessupporting
confidence: 93%
“…The ∆v Lyα,r value has been measured in more than 60 LAEs (McLinden et al 2011;Finkelstein et al 2011;Hashimoto et al 2013;Guaita et al 2013;Chonis et al 2013;Shibuya et al 2014b;Song et al 2014;Erb et al 2014). These studies have shown that LAEs at z ∼ 2 − 3 have a mean ∆v Lyα,r of ≃ 200 km s −1 , which is significantly smaller than that of LBGs at a similar redshift, ∆v Lyα,r ≃ 400 km s −1 (e.g., Steidel et al 2010;Rakic et al 2011;Kulas et al 2012).…”
Section: Lyα Main Red Peak Velocity Offsets ∆Vlyαrmentioning
confidence: 99%
“…In starburst galaxies, the width of the intrinsic Lyα line is lower than 100 km s −1 (Teplitz et al 2000;Baker et al 2004;Erb et al 2003;McLinden et al 2011), which implies an expansion velocity v exp lower than 200 km s −1 in the ISM. We illustrate this limit in Fig.…”
Section: Physical Conditions Needed In the Ismmentioning
confidence: 99%